Programa de gestão ambiental para o processo de mineração no município de São Domingos do Sul RS. - Poleto, Luciane (2003)
This job presents a Program of Environmental Administration for the mining process in the municipal district of São Domingos do Sul RS. This work had as tool the methodology followed in the Analysis of the Cycle of Life ALC. This methodology contemplates: a diagnosis on the rising of data of the local reality, reaching social, political, economic and environmental aspects a rising georeferencial (see Illustration 03) of the existent mines (forty in the total); the application of the norms ISO 14001 14004 and 14040 to 14044; and the opening legislation and it plows in the mining. The extracted product is the rock granófiro, used in the construction of houses, roadways, foundations, roofs, trashcans, and others. It is extracted in a very manual or handmade way. Due to that, the final product is not very valued in the district of Santa Gema. It is realized that the lack of technology makes the difference, because the gross product is sold to the neighbor town, Paraí, where the rock is cut out with high-technology Italian machines. These machines have standardized measures according to the requests. Besides the lack of technology, it is visualized by the photographic file that the process of extraction of the rock faces environmental problems, as the inadequate destiny of the dump or resulting residue of the activity, which are causing inundation of the rivers that are located close to the rivers. In this sense, it is desired to decrease the environmental passives, with the elaboration of an environmental administration program for the mining process.